Canadian Work-Related Values - Casserly, M. Catherine (Canadian Journal of Counselling and Psychotherapy, 1980)
This paper summarizes the Canadian literature used in the development of the Canadian Work Values Survey. This is an instrument which is being designed to identify work-related values In Canada. The research related to the test development is part of an international project led by Donald E. Super to examine the role and importance of work in people's lives. The literature highlights that while Canadians hold many values in common with other industrialized countries, they place special emphasis on such work-related values as ability development, cultural identity, risk-taking and the opportunity for impact. It focuses on research dealing with class, cultural, sex and age differences within Canada as well as overall expressed job satisfaction.